Tinjauan Pelaksanaan Pembayaran Non Tunai pada Belanja Bantuan Sosial: Studi Kasus Program Keluarga Harapan - Muhammad Heru Akhmadi (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2017)
Social Assistance is a government instrument in carrying out a fiscal policy for reducing poverty. Cash transfer, which has been given to social assistance recipients of the hope familiy program, has weaknesses in area both social and economical benefits, especially for financial inclusion program. To cope with the weaknesses, the government has adopted non-cash payments since 2016. This research investigated key success factors in implementing non-cash payments by using the hope family program as an sample. The result findings indicated that there was a need to make some adjustments, such as improving payment mechanism, improving understanding of financial information for social assistance recipients, adopting NIK as a basis for social assistance recipients database, simplificating of institutional bodies, integrating social assistance programs, and developing of information system for social assistance. Abstrak Bantuan Sosial merupakan instrumen pemerintah dalam melakukan kebijakan fiskal untuk menanggulangi kemiskinan. Sistem Pembayaran Tunai yang diberikan kepada penerima Bantuan Sosial Program Keluarga Harapan masih memiliki kelemahan baik dari sisi manfaat sosial maupun manfaat ekonomi khususnya program inklusi keuangan. Mengatasi hal ini, pemerintah melakukan ujicoba pembayaran non tunai sejak tahun 2016. Penelitian ini mencoba menggali faktor-faktor kesuksesan dalam sistem pembayaran non tunai dengan kasus Program Keluarga Harapan. Hasil penelitian menunjukkan bahwa perlunya melakukan penyesuaian seperti penyempurnaan mekanisme pembayaran, peningkatan pemahaman keuangan penerima bantuan, penggunaan NIK sebagai basis data penerimaan bantuan sosial, penyederhanaan kelembagaan, integrasi program bantuan sosial serta pengembangan sistem informasi bantuan sosial.